Low-temperature magnetoresistance of GaSb whiskers - Druzhinin, A.; Ostrovskii, I.; Khoverko, Yu.; Liakh-Kaguy, N. (Физика низких температур, 2017)
Transverse and longitudinal magnetoresistancies in n-type GaSb whiskers with different doping concentration (Te) in the vicinity to the metal-insulator transition (MIT) from metal side of the transition were studied in the temperature range 1.5–60 K and magnetic field 0–14 T. Shubnikov-de Haas oscillations in GaSb whiskers at low temperatures were revealed in magnetic field range 2–12 T. The oscillation period 0.025 T⁻¹ was found at various doping concentration in GaSb whiskers. The effective mass of electrons m c = 0.041 m ₀ and Dingle temperature of about 7.5 K were found in GaSb whiskers with impurity concentration in the vicinity to MIT. The presence of negative magnetoresistance in GaSb whiskers with the impurity concentration in the nearest approximation to MIT with resistivity ρ ₃₀₀ K = 0.0053 Ω cm was observed and associated with weak localization. Besides for the whiskers a resistance minimum was observed at temperature about 16 K that is connected with Kondo effect. Magnetoresistance studies of n-type conductivity for GaSb whiskers revealed the crossover from weak localization to antilocalization in the temperature range of 1.4–4.2 K and magnetic fields below 1 T.